1993
DOI: 10.2172/10191341
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent liquid ion exchange with chabazite zeolites

Abstract: vi LIST OF SYMBOLS a geometry constant; 1 for planar, 2 for cylindrical, 3 for spherical a,t isotherm constant for cation i a01 constant in Equation 69 a2i constant in Equation 69 Ai_ collocation constant to replace gradient A, equivalent fraction of cation A in solution phase A_ equivalent fraction of cation A in solid phase bi isotherm constant for cation i Bj_ collocation constant to replace Laplacian operator B, equivalent fraction of cation B in solution phase Bz equivalent fraction of cation B in solid p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…It is obviously due to the greater pore volume and pore size at higher PVP content. The diffusion coefficients of the both ions in composite beads increase up to 3 times with increasing PVP content, and they are of the order of 10 -8 cm2/sec, as obtained roughly from a homogeneous diffusion model [15]. Fig.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…It is obviously due to the greater pore volume and pore size at higher PVP content. The diffusion coefficients of the both ions in composite beads increase up to 3 times with increasing PVP content, and they are of the order of 10 -8 cm2/sec, as obtained roughly from a homogeneous diffusion model [15]. Fig.…”
Section: Resultssupporting
confidence: 63%
“…The higher is the selectivity of certain exchanger for given ions (Sr 2+ in this case), the more tightly are those ions bound to the sorption site. If their hydrated effective radius is large enough, the preoccupied ions can slow down the diffusion of non-sorbed ions in the pores [15].…”
Section: Resultsmentioning
confidence: 99%
“…In past zeolite column experiments, small columns of 1-8 cm inner diameter were often used [12][13][14][15]. It was found that the columns for which the bed aspect ratio of the bed length to the inner diameter was less than 1 tended to perform poorly, because it is difficult to distribute the feed uniformly [16].…”
Section: Small-column Equipmentmentioning
confidence: 99%
“…Especially, when a number of isotherms with different theoretical assumptions and approach to equilibrium data modeling show reasonable fit for the same data set, careful Table 3. Adjustable parameters and goodness of fit information for adsorption isotherms applied on Cd-clinoptilolite interaction Isotherms As-received (GC) Pretreated (pGC) (26) argues that choice of the most representative isotherm model for an experimental system should depend mainly on the adsorbent (i.e., incorporating heterogeneous nature of zeolites) and adsorbate characteristics. For example, the constants in L, F, RP, and T models do not give any idea about the physical or chemical nature of sorption process.…”
Section: K Gedik and I Imamoglu 1196mentioning
confidence: 99%
“…For example, the constants in L, F, RP, and T models do not give any idea about the physical or chemical nature of sorption process. On the other hand, the Polanyi potential theory based DA model and its special form of DR (n ¼ 2) compensate this deficiency in estimating the equilibrium behavior of porous materials (26). These models suggest the adsorption process via micropore volume filling rather than layer-by-layer adsorption on pore walls (23) and hence are more applicable and meaningful when porous sorbents are concerned (18).…”
Section: K Gedik and I Imamoglu 1196mentioning
confidence: 99%